(untitled) (Singapore, 1999)
This invaluable collection of essays pays tribute to Dan Tsui, 1998 Nobel laureate in Physics. It paints a portrait of his outstanding personal attributes through the eyes of his friends and relatives. In addition, it provides a record of the environment which accompanied him in his search for knowledge. This book, capturing Dan Tsui's experience and joy of the search for knowledge, will inspire scholars of all ages.
Keywords: Physicists,Knowledge systems and research, Inc.,Nhà vật lý,Hệ thống tri thức và nghiên cứu,Knowledge, Theory of.,Lý thuyết về tri thức; Biography,Tiểu sử